ALUR DALAM NOVEL "MELANGKAH KE SEBERANG" KARYA KARINA NURHERBYANTI HERBOWO - Yolanda; Fatimah; As’ad (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2024)
The purpose of this study was to determine the stages of the plot in the novel Melangkah ke Seberang by Karina Nurherbyanti Herbowo and to implement them in Indonesian language learning. This study uses a qualitative descriptive research approach. The research technique used is content analysis technique. Based on the research that has been done regarding the plot in the novel Melangkah ke Seberang by Karina Nurherbyanti Herbowo, the results show that the stages of the plot in this novel are 75 findings, consisting of the exposure stage as much as 24 data with a percentage of 32%, the initiation stage as many as 11 data with a percentage of 14.67%, the ascending stage of 7 data with a percentage of 9.33%, the climax stage of 19 data with a percentage of 25.33%, and the dissolution stage of 14 data with a percentage of 18.67%. From the data obtained, it can be concluded that the exposure stage has more numbers than the other stages in the novel.